Validation of a Discovery Learning Based Instructional Module for Grade X Vocational High School Students - Juhentriana Samaloisa; Refnywidialistuti Refnywidialistuti; Yuliani Fitri (The Future of Education Journal, 2026)
This study aims to develop and validate a Discovery Learning-based learning module for Phase E students at SMK Negeri 2 Padang. The developed module is designed to improve students' self-directed thinking skills and conceptual understanding through a process of independent discovery. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Module validation was conducted by two validators. The validation results showed that the developed module obtained an average score of 0.9 from material experts with a "Very High" category and 0.73 from language experts with a "Very High" category. Thus, the developed Discovery Learning-based learning module is suitable for use in the learning process at SMK Negeri 2 Padang.